John Brown in memory and myth - Daigh, Michael, 1977- (McFarland & Company, Incorporated, Publishers, 2015)
"This is the story of John Brown, the age he embodied and the myth he became, and how the tragic gravity of his actions transformed America's past and future. Through biographical narrative, his life and legacy are discussed as a study in metaphor and power, and the nature of historical memory"--